2017
DOI: 10.7748/ns.2017.e10539
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ experience of research during clinical placements

Abstract: Aim To investigate pre-registration nursing students' experience of research during clinical placements, and to identify any positive aspects or barriers to gaining experience of research during clinical placements. Method Qualitative, phenomenological, semi-structured interviews were undertaken with preregistration degree-level nursing students. The students were attending one university in the east of England, and were on clinical placements at one of three hospital sites in two trusts. Data were reviewed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Code: Professional Standards of Practice and Behaviour for Nurses, Midwives and Nursing Associates (Nursing and Midwifery Council 2018) states that nurses must 'always practise in line with the best available evidence'. Although clinical research is crucial to generating this evidence and research nurses are central to the delivery of such research, there is little in the literature to suggest that this topic is routinely included in undergraduate nurse education curricula (Whitehouse 2017).…”
Section: Clinical Research In Undergraduate Nurse Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Code: Professional Standards of Practice and Behaviour for Nurses, Midwives and Nursing Associates (Nursing and Midwifery Council 2018) states that nurses must 'always practise in line with the best available evidence'. Although clinical research is crucial to generating this evidence and research nurses are central to the delivery of such research, there is little in the literature to suggest that this topic is routinely included in undergraduate nurse education curricula (Whitehouse 2017).…”
Section: Clinical Research In Undergraduate Nurse Educationmentioning
confidence: 99%
“…Similarly, Mason (2018) recognised that pre-registration experiences of clinical research can inspire the research nurses of the future. However, Whitehouse (2017) suggested that nursing students' clinical research placements can vary in quality and that the topic of research nursing should be introduced earlier in undergraduate nurse education programmes to address misconceptions about it.…”
Section: Clinical Research In Undergraduate Nurse Educationmentioning
confidence: 99%
“…Findings from the nursing profession report that students negatively perceive research theory but that this perception changes when students experience the application of research methods to placement. After having had this experience, students reported an increase in confidence in applying research methods theory to practice and demonstrated a clearer appreciation of the benefits that research can have for clinical practice (Whitehouse, 2017). The lack of confidence in understanding evidence-based theory is something that student SLTs have also reported (Spek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%